Analysis of the Application of the Balanced Scoredcard as an Alternative to Performance Measurement Tools at Lembaga Penjaminan Mutu Pendidikan (LPMP) in South Sulawesi - Sahade Sahade; M. Yusuf A. Ngampo; H. Abd Rijal (Seminar Nasional LP2M UNM, 2021)
Abstarct. The purpose of the study was to determine the application of the balanced scorecard method as an alternative tool for measuring institutional performance. The variables of this research are the Balanced Scorecard and the performance of the institution. The type of research used is qualitative research by describing the value of the balanced scorecard indicators quantitatively which is viewed from four perspectives, namely financial, customer, internal business processes and learning and growth perspectives. The population is all budget reports, and the level of performance achievement of the Lembaga Penjaminan Mutu Pendidikan (LPMP) in South Sulawesi and the sample is data on Realization Targets with Budget Efficiency Levels and Targets with Realized Performance Achievement Levels in 2018 and 2019. Based on the results of research and qualitative data analysis, it was obtained that the financial perspective, namely Target Realization and Budget efficiency levels in 2018 and 2019, had used the funds that had been budgeted for each activity efficiently, so that the financial perspective of LPMP in South Sulawesi achieved good results. Furthermore, the customer perspective shows that customers are satisfied with the services provided with an index achieved of 2,800 points in the interval of 2,556.8 to 3,158.4 points so that it can be categorized as satisfied. Furthermore, the perspective of internal business processes, which also shows that the performance of the institution has not achieved good results. This is evidenced by the Target and Realization of Performance Achievement Levels during 2018 and 2010. The next perspective is learning and growth which has two performance measurement tools, namely Employee Satisfaction which is categorized as quite satisfied and Learning index which is categorized as satisfied. This shows that the level of learning at the Lembaga Penjaminan Mutu Pendidikan (LPMP) in South Sulawesi has reached the expected standard. While quantitatively seen from the 4 (four) perspective the Balanced Scorecard can be said to be good because the Lembaga Penjaminan Mutu Pendidikan (LPMP) in South Sulawesi reaches 75% of the set standards or as many as 3 (three) of the 4 (four) indicators used in the Balanced method. scorecard. among others: 1) customer satisfaction, 2) budget efficiency and work efficiency, 3) employee satisfaction and 4) learning index. These results indicate that the overall performance of the institution is in the good category. So that the proposed hypothesis is declared